2005
DOI: 10.1186/1745-0179-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundFew epidemiological studies have focused on the occurrence of positive mental health, and those comparing several countries practically non-existent. This study presents comparative findings of positive mental health in 11 EU countries or regions, based on the Eurobarometer 2002 (autumn) survey.MethodThe sample (n = 10,878) represents the general population, aged 15 or over, of 11 European countries or regions (all old EU Member States except Denmark, Greece, Ireland, Finland and Great Britain which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 15 publications
6
33
0
1
Order By: Relevance
“…Some studies of older people suggest a decline in life satisfaction and quality of life after age 65 or 70 (Netuveli et al, 2006;Ploubidis & Grundy, 2009); others find little variation with age after control for factors such as health, marital status, and income (Larson, 1978). Studies of national differences show that within Europe the populations of the Nordic countries report the highest levels of happiness and those in East European countries the lowest (Djankov, Nikolovab, & Zilinskyc, 2016;Lehtinen, Sohlman, & Kovess-Masfety, 2005;Ploubidis & Grundy, 2009). Steptoe et al (2015) analysed data from the 2006-2010 rounds of Gallup's World Poll and found notable differences between world regions in associations between age and various aspects of subjective well-being.…”
Section: Other Correlates Of Subjective Well-being Among Older Peoplementioning
confidence: 99%
“…Some studies of older people suggest a decline in life satisfaction and quality of life after age 65 or 70 (Netuveli et al, 2006;Ploubidis & Grundy, 2009); others find little variation with age after control for factors such as health, marital status, and income (Larson, 1978). Studies of national differences show that within Europe the populations of the Nordic countries report the highest levels of happiness and those in East European countries the lowest (Djankov, Nikolovab, & Zilinskyc, 2016;Lehtinen, Sohlman, & Kovess-Masfety, 2005;Ploubidis & Grundy, 2009). Steptoe et al (2015) analysed data from the 2006-2010 rounds of Gallup's World Poll and found notable differences between world regions in associations between age and various aspects of subjective well-being.…”
Section: Other Correlates Of Subjective Well-being Among Older Peoplementioning
confidence: 99%
“…Firstly, these instruments have been mainly developed and validated in Western populations and challenges with validity and appropriateness of adopting such measures across varied cultures have been reported [12,13]. Secondly the content of these measures relies either on literature, item reduction using item pool and expert panels [7,8,10,14], although it is generally recommended that the content of self-reported measures of well-being and quality of life be developed in the end-user [15,16]. In addition, most of the instruments either study a particular domain in greater detail using a lengthy questionnaire or are too short to provide meaningful comparisons and detection of change across different domains.…”
Section: Introductionmentioning
confidence: 99%
“…Positive mental health assessment in the European Union (2005) was low in Italy, Portugal, France, and Sweden, while it was moderate to high in Germany, Spain, and Netherlands [8]. The results indicate that positive mental health status needs more attention in many countries.…”
Section: Introductionmentioning
confidence: 84%